Seleção recorrente em feijão visando resistência ao mofo branco em casa de vegetação - Lopes, Fernanda Souza (2017)
The research aims to estimate the selection gain of cycle XII of recurrent selection in greenhouse and to compare the efficiency of markers assisted selection (MAS) with phenotypic selection for white mold resistance. 900 plants were growed in greenhouse and in four weeks, the most aggressive isolate (isolate 27) of Sclerotinia sclerotiorum was inoculated. Two inocula were made per plant at 2.5 cm from the node, by the straw test procedure. One week after inoculation, the plants were evaluated by a diagrammatic scale and the most susceptible were eliminated. The 79 most resistant S0:1 progenies were seeded in the field together with two controls, Corujinha (susceptible) and Cornell 605 (resistant), using a simple 9x9 lattice design and were inoculated by the straw test and evaluated again. The best 21 S0:2 progenies were seeded in the field together with the best progenies of the cycles IX, X, XI and the two controls in a 6 x 6 triple lattice design. Considering the best progenies of the four cycles the genetic gain was 6.67% per cycle, although between the cycles XI and XII it was 12.17% indicating greater efficiency of the mass selection of the plants S0 in greenhouse. The gain of phenotypic selection among the S0:1 progenies of the cycle XII was16.15% and using the marker assisted selection it was 5.05%, indicating that phenotypic selection is more efficient. Therefore, the efficiency of MAS was only 4.76%. Considering the plant architecture and grain type, the estimated accuracy was average, but the coefficient of variation was low, indicating that probably the low genetic variability among the progenies may have underestimated the accuracy and consequently the accuracy. The high genetic uniformity did not allow to distinguish the progenies for grain yield, however, the evaluation of the architecture, weight and type of grains allowed the selection of promising progenies, with carioca grain type, up right architecture, good productivity and hight resistance to white mold.